2021
DOI: 10.1021/acs.jnatprod.0c01292
|View full text |Cite
|
Sign up to set email alerts
|

Diterpenoids with Aromatase Inhibitory Activity from the Rhizomes of Kaempferia elegans

Abstract: Investigation of bioactive compounds from the rhizomes of Kaempferia elegans led to the isolation and characterization of ten new diterpenoids, namely, five 12,13-seco-diterpenoids named elegansins A–E (1–5) and five new abietanes, elegansols A–E (6–10), together with seven known diterpenoids (11–17). The structure elucidation of the new compounds was achieved by HRESIMS, NMR, and ECD spectroscopic analysis. Compounds (1–5) are the first examples of 12,13-seco-diterpenoid-type compounds representing a decalin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…The above information demonstrated two structural units (C-7–C-12 and C-1–C-5), and their linkage via C-6 was established by the HMBC correlations from H-13b to C-5, C-6, and C-7. To match the other two degrees of unsaturation and deshielded NMR signals of C-2, C-6, C-13, and H 2 -13, the remaining two oxygen atoms were situated between C-2 and C-6 and between C-2 and C-13, respectively, and the latter further supported the HMBC correlation from H-13a to C-2. OH-5 and C-13 were oriented on the same face of the tetrahydropyran ring by the NOE correlations from OH-5 to H-13a, while H-5 and C-7 were allowed to be on the other face by the NOE correlation of H-5/H-7a.…”
Section: Resultsmentioning
confidence: 76%
“…The above information demonstrated two structural units (C-7–C-12 and C-1–C-5), and their linkage via C-6 was established by the HMBC correlations from H-13b to C-5, C-6, and C-7. To match the other two degrees of unsaturation and deshielded NMR signals of C-2, C-6, C-13, and H 2 -13, the remaining two oxygen atoms were situated between C-2 and C-6 and between C-2 and C-13, respectively, and the latter further supported the HMBC correlation from H-13a to C-2. OH-5 and C-13 were oriented on the same face of the tetrahydropyran ring by the NOE correlations from OH-5 to H-13a, while H-5 and C-7 were allowed to be on the other face by the NOE correlation of H-5/H-7a.…”
Section: Resultsmentioning
confidence: 76%
“…In turn, the NOESY correlations between H-4/H-6 and H-6/H-5a indicated that H-4, H-5a, and H-6 are all located at the same side of the ring. Furthermore, NOESY correlations of H- 7/H-8, H-7/H-5b, and H-8 resonated as a broad singlet, implying a small coupling constant of H-8 with H-7, 17 which suggested that H-5b, H-7, and H-8 were on the other side of the molecule. The absolute configuration of 1 was confirmed by comparison of the experimental and calculated ECD data (Figure 3).…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…Although a variety of procedures have been reported for selective alcohol dehydration, regioselective conversion of alcohol 2 to alkene 3a is a challenge. Three potential alkenes, Δ , ( 3a ), Δ , ( 3b ), and Δ , ( 3c ), could be formed, and alkene 3b is the thermodynamically stable product due to the conjugation of its CC double bond and aldehyde group. Indeed, alkenes 3a and 3c can be converted to alkene 3b under ultrasonic treatment via an aldehyde-enol tautomerization (Scheme ).…”
Section: Results and Discussionmentioning
confidence: 99%
“…In summary, we described the facile synthesis of three natural products: ustusal A (first synthesis, 11 steps in the longest linear sequence from the abundant feedstock chemical (+)-sclareolide), (−)-albrassitriol (10 steps from (+)-sclareolide), and elegansin D (first synthesis, 9 steps from (+)-sclareolide). The notable characteristics of the synthesis of these natural products are as follows: (i) Development of regioselective dehydration procedures of aldehyde alcohol 2 to alkenes Δ , ( 3a ), Δ , ( 3b ), and Δ , ( 3c ), respectively. (ii) Development of a singlet oxygen [4 + 2] cycloaddition for simultaneously introducing the 1,4- cis -hydroxyl groups with the desired stereoselectivity to the C6- and C9-positions of ustusal A and (−)-albrassitriol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation